Anti stress activity of cissus quandanguluris - SAYED MAMOON HUSSAIN; ROSHAN S (International Journal of Pharma and Bio Sciences, 2019)
The present study was carried to evaluate ethanolic extract of Cissus quadrangularis (ECQ) on swimming endurance time and anoxia tolerance test in mice and cold and immobilization stress on albino rats foranti stress activity. The effect of ECQ at a dose of 300 and 500 mg/kg body weight (po) was determined for swimming survival and anoxia tolerance time in mice, in cold and immobilization stress. Estimation of glucose, cholesterol, triglycerides and BUN, weight of organs such as, liver, spleen, testes, adrenal glands, WBC and DLC counts were compared with Gerifort Syrup (2 ml/kg b.w). Results showed 500mg ECQ showed significant (p<0.001) increase in swimming time and anoxia tolerance time. ECQ showed significant (p<0.001) decrease in blood glucose, cholesterol, triglyceride (TG), plasma cortisol and BUN levels and also decreased the weight of organs in both stress induced models. It also showed a significant (p<0.05) decrease in the weight of adrenal glands. A significant (p<0.01) decrease in WBC count, polymorphs and monocytes with a decrease in lymphocytes (p<0.05) and eosinophils were also observed, compared to the control and gerifort group. Thus the obtained results revealed that the Cissusquadrangularis has a significant anti stress activity